Implications of the Expansion of Criminal Jurisdiction for State Sovereignty in Counter-Terrorism under the Criminal Code - Subihat, Ihat (Intellectual Law Review (ILRE), 2025)
The transnational nature of terrorism poses significant challenges to the traditional territorial concept of criminal jurisdiction and directly affects the principle of state sovereignty. The expansion of criminal jurisdiction under Law Number 1 of 2023 concerning the Indonesian Criminal Code (KUHP) raises legal questions regarding the extent to which a state may exercise jurisdiction in combating terrorism without infringing upon the sovereignty of other states. This study aims to analyse the implications of the expansion of criminal jurisdiction on state sovereignty in the context of counter-terrorism based on the 2023 KUHP and its conformity with principles of international law. This research employs a normative juridical method, using statutory, conceptual, and case approaches through an examination of the 2023 KUHP, counter-terrorism legislation, and relevant doctrines and international legal instruments. The findings indicate that the expansion of criminal jurisdiction in the 2023 KUHP is not arbitrary but is grounded in the principles of active nationality, passive nationality, and the protection of state interests, all of which require the existence of a genuine legal link. Such expansion is primarily situated within the scope of jurisdiction to prescribe and is implemented subject to the principles of non-intervention and international legal cooperation. This study concludes that the expansion of criminal jurisdiction under the 2023 KUHP reconstructs the concept of state sovereignty in a functional and responsible manner, while simultaneously strengthening Indonesia’s position within the global counter-terrorism legal regime without undermining state sovereignty or human rights.